Reformasi Mazhab Fiqh Terhadap Tuntutan Penyelesaian Masalah Konteporer - Adil, Syafaat Muhammad Wildan; Maloko, M. Thahir; Hasan, Hamzah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The renewal of Islamic law essentially rests on something that already exists, then undergoes a qualitative change as a product of interactions in community life. It can be said that the process of Islamic legal renewal is viewed as something autonomous, but it also interacts with other elements in society so that it becomes interdependent. Therefore the concept of renewal of Islamic law demands the presence of an adaptive attitude, with the social conditions of the society in which it interacts. Thus, the renewal of Islamic law must be undertaken in response to the demands of change occurring among the society. The reform of schools in Islamic Law is carried out as an attempt to implement the Islamic law of Ijtihad, namely the results of ijtihad scholars who have lost their actual power in the context of today by re-studying by the competent authorities and ijtihad against new issues that have never been discussed by scholars. In the course of history, Islamic law has been a dynamic and creative force. This is characterized by the presence of various sects with different patterns and characteristics, according to the socio-historical and political background in which they grew and developed. In the paradigm of classical jurisprudence there are five principles that allow Islamic law to develop according to time namely 1) Principle of Ijma, 2) Principle of Qiyas, 3) Principle of Maslahah Mursalah, 4) Principle of maintaining Urf. Islamic law